2004
DOI: 10.21273/jashs.129.6.0896
|View full text |Cite
|
Sign up to set email alerts
|

Bending Alters Water Balance and Reduces Photosynthesis of Rose Shoots

Abstract: Shoot-bending has become a standard cultural practice in cut-flower rose (Rosa hybrida L.) production. Physiological effects of shoot-bending on leaf net photosynthesis (A), stomatal conductance (gs), transpiration rate (E), and stem water potential (ψ) were investigated for rose plants. With saturating light conditions, shoot-bending decreased rates of A Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
(22 reference statements)
1
15
1
Order By: Relevance
“…both occurred in the 5% treatment, indicating a potential physical blockage hindering the movement of water. The degree of potential xylem vessel blockage in this study appears to be similar to or less than the xylem blockage resulting from other physical damages such as stem bending (Kim et al, 2004). Previous studies have also shown xylem colonization and blockage in woody stems caused by various Phytophthora pathogens (Brown and Brasier, 2007;Parke and Lewis, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…both occurred in the 5% treatment, indicating a potential physical blockage hindering the movement of water. The degree of potential xylem vessel blockage in this study appears to be similar to or less than the xylem blockage resulting from other physical damages such as stem bending (Kim et al, 2004). Previous studies have also shown xylem colonization and blockage in woody stems caused by various Phytophthora pathogens (Brown and Brasier, 2007;Parke and Lewis, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…The key finding of this work is that crops may exhibit horticulturally beneficial responses at mild to moderate levels of water stress (Lampinen et al, 1995(Lampinen et al, , 2001(Lampinen et al, , 2004, and hence we believe that this plant-based approach to irrigation scheduling will allow us to recommend a strategy of RDI that will appeal to growers and also will benefit the environment by reducing water and nitrogen fertilizer leaching below the root zone. Initial work using this method has also been successful in measuring stress in native oak species (Shackel and Gross, 2002) and ornamental roses (Kim et al, 2004). A series of experiments were performed to test for a broad applicability of SWP to water management under field conditions in prunes and almonds and to determine whether SWP had a consistent relation to g S in almonds under both irrigated and rain-fed (drought) conditions.…”
mentioning
confidence: 99%
“…However, A max of the most illuminated leaf in upright shoots ( A 0,upright ) was higher than in bent shoots ( A 0,bent ) ( Supplementary data Fig. S6 ), indicating that shoot bending may decrease photosynthetic capacity of leaves in bent shoots, which is also found by others and in other crops ( Schubert et al ., 1995 ; Kim et al ., 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations are proposed to explain the lower photosynthesis of leaves in bent shoots. Kim et al . (2004) found that the xylem tissue of rose bent shoots was damaged due to bending, and this could reduce hydraulic conductivity of bent shoots and decrease photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation